(untitled) (Journal of Education and Development, 2024)
This literature review compared faculty use of Moodle Learning Management System in the Caribbean with global practices to determine the impact of the pandemic on LMS adoption. The findings reveal that while there were similarities regarding access to devices and reliable internet, students at universities in the Caribbean and the developing world were at a greater disadvantage. In the developed world, there were also significant disparities in rural versus urban areas. The pandemic provided an impetus for using educational technology at universities; however, the digital divide and lack of devices, reliable internet, and electricity hampered the full use of LMSs.